Strategi Dinas Pemadam Kebakaran dan Penyelamatan Kota Surabaya dalam Pelayanan Penanganan Kebakaran - Yariza Tasya Ferziah; Ananta Prathama (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2023)
The city of Surabaya is the second largest city in Indonesia with a fairly high level of population density, with the existence of this population density causing residential density that can cause slums and have an impact on fires. This is the responsibility and commitment of the Surabaya City (DPKP) in providing firefighting handling services to the community. This study is intended to describe how the strategy of the Surabaya City DPKP in firefighting handling services. This research method uses qualitative methods with interview data collection techniques, observation and documentation. The theory used in this study is strategy management by Fred R David (2019) based on three focus indicators, namely strategy formulation, strategy implementation and srateg evaluation. The results of this study show that the strategy used by the Surabaya City DPKP can be said to be succeeded by getting the Commendable Public Innovation award in 2022 through a 7-minute response time program with the support of the vision and mission, the strength of human resources and infrastructure.